This Was Actually Fun!: Engaging Users in Conversations about Digital Literacy - Rigling, Lillian; Johnson, Erin; Goldhawk, Madisson (Université d'Ottawa | University of Ottawa, 2018)
This interactive presentation highlights pop-up programming designed to improve 21st century digital literacies. The session includes an overview of activity development and reflections on its success. Participants will explore light-touch digital literacy games on their personal devices and take home tools to recreate similar programming at their library.